ANALYSIS OF SUSTAINABLE WATER RESOURCES MANAGEMENT BASED ON THE POTENTIAL WATER AVAILABILITY IN THE SEMI-ARID AREA OF KUPANG, INDONESIA - Marlin A Koan; Jakobis Johanis Messakh; Soetedjo IN P (Universitas Trisakti, 2020)
Aims: This study discusses water resources management based on water discharge potential of the Oebobo-Liliba watershed in Kupang City, East Nusa Tenggara, Indonesia. Methodology and Results: River water discharge was analyzed based on hydrological data of a span of 10-years. Average rainfall was calculated using the arithmetic mean method, and potential evapotranspiration (ETo) was calculated through Penman Modification with CROPWAT 8.0. The discharge analysis was conducted through a Mock method. Change in land cover was rendered using related land maps from year 2008 and 2018. Management of agricultural land was discussed through a descriptive analysis. The results showed an average monthly discharge of 0.667 m3/sec. The need for clean water is rendered to be 170 liters/person/day, and the discharge requirement of 90% = 281 liters/sec is concluded to be able to meet the community's clean water needs which amounts to 142,569 people. The total area of paddy fields is 5.38 Ha with water requirements of 1.5 liter/sec/ha, where 80% or 348 Liter/sec can be used to irrigate 232 hectares of paddy. Further results show that land cover in dryland forests decreased from 15% to 10%, settlements increased from 20% to 49%, and shrubs diminished from 20% to 0%. Conclusion, significance and impact study: The minimum debit trend shows a declining trend, while the maximum discharge trend shows an inclining trend. This research concludes that water discharge is adequate to meet community needs yet requires proper water resources management strategy from upstream to downstream of the watershed.